An Analysis of Preparedness and The Impact of Floods in India (Indian Journal of Public Health Research & Development, 2020)
India is the most flood prone country in the world with instances of at least 15 major occurrences in the lastdecade. Apart from loss of lives and property, the country suffers huge economic, infrastructural as wellas environmental damage on a yearly basis. In addition, several indirect and prolonged effects of floodsaffect the country as well. This is coupled with facilitating factors such as global warming and unplanneddevelopment in flood plains. Understanding the gravity of the situation, the government of India enactedthe Disaster Management Act in 2005 subsequently forming the National Disaster Management Authority.This body has developed guidelines for flood mitigation at national, state as well as at regional levels. Thecountry needs to develop effective flood mitigation system in order to reduce the periodic damage enduredby the people and the state.
Keywords: Flood mitigation; NDMA; Impact of floods; flood preparedness